Analysis of The Effect of Cities on Economic Growth Through Ports: A Case Study of Indonesian Port - Pasaribu, Dominggo; Nasution, Zulkifli; Lubis, Satia Negara; Absah, Yeni (International Conference on Sciences Development and Technology, 2023)
Port is an area where there are economic and trade activities and is also a transportation hub between land and sea modes (interface). Port development aims to increase port productivity in anticipating an increase in the volume of service demand stimulated by economic and trade developments. Development is carried out through investment activities in developing port infrastructure in increasing terminal capacity and equipment and other resources. Port is expected to contribute to the growth of cities as key regional development centers, driving economic expansion. This study examines the effect of ports on economic growth and assesses its role in mediating the effect of cities on economic development in Indonesia, the largest archipelagic country in the world. The study employed a quantitative approach, collecting panel data from 50 cities and ports involved in loading and unloading activities in Indonesia, and analyzing the data using Structural Equation Modeling. The research findings demonstrate that ports have a positive and significant effect on economic growth, and mediates the effect of cities on economic development in Indonesia. These results provide empirical support for enhancing policies and developing more effective economic strategies for archipelagic countries, based on the interconnected variables. Investments in appropriate infrastructure and collaborative stakeholder strategies can deliver substantial and sustainable port development and economic benefits.